2007
DOI: 10.1262/jrd.19041
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Proliferation and Apoptosis in the Granulosa and Theca Interna Cells of the Bovine Cystic Follicle

Abstract: Abstract. The aim of the present study was to examine the frequencies of cell proliferation and death of granulosa and theca interna layers during development of cystic follicles in order to understand the mechanisms of cystic follicle formation. Paraffin sections of cystic follicles were immunostained with antibodies against proliferating cell nuclear antigen (PCNA) and cleaved caspase-3 in order to observe proliferating and apoptotic cells, respectively. The concentrations of estradiol-17β and progesterone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 27 publications
6
44
1
Order By: Relevance
“…Previous studies found that the mRNA levels for cyclins D1 and E in samples of the follicular wall are lower in cystic follicles than in healthy tertiary follicles (Isobe & Yoshimura 2007. Similarly to the results found in induced follicular cysts in rats in different experimental models (Table 1; Baravalle et al 2006, tertiary follicles of cows show an intense proliferation in the basal area of the granulosa layer, whereas in atretic and cystic follicles proliferation declines (Isobe & Yoshimura 2007.…”
Section: R258 H H Ortega and Otherssupporting
confidence: 56%
“…Previous studies found that the mRNA levels for cyclins D1 and E in samples of the follicular wall are lower in cystic follicles than in healthy tertiary follicles (Isobe & Yoshimura 2007. Similarly to the results found in induced follicular cysts in rats in different experimental models (Table 1; Baravalle et al 2006, tertiary follicles of cows show an intense proliferation in the basal area of the granulosa layer, whereas in atretic and cystic follicles proliferation declines (Isobe & Yoshimura 2007.…”
Section: R258 H H Ortega and Otherssupporting
confidence: 56%
“…Many studies have demonstrated changes and pathogenetic mechanisms evolved in follicular cyst in cattle (Garverick 1997, Isobe & Yoshimura 2007, Ortega et al 2007b, Monniaux et al 2008, Ortega et al 2008, Rey et al 2010), rat (Anderson & Lee 1997, Ortega et al 2007a, Salvetti et al 2009) and women (Abbot et al 2002, Ortega et al 2009b), but few investigations have been conducted in the genesis of this condition in sows. The current study shows that the formation of ovarian cysts in sows is associated to alterations in the expression of some cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, these concentrations change dramatically in the absence of granulosa cells [11,12]. Since E2 is produced by granulosa cells, elimination of these cells reduces the E2 concentration; E2 concentration therefore represents a check point for resolution of the stage of the cystic follicles [9,12]. The FCOs used in this study showed granulosa cell layers, high concentrations of E2 in their follicular fluid, and no significant difference from normal ovaries with respect to apoptotic cells indicated by TUNEL staining.…”
Section: Bovine Follicular Cystic Ovarymentioning
confidence: 57%
“…Follicular cysts were diagnosed based on macroscopic and endocrinological characteristics [8]. The follicular walls of the cysts were thin and translucent [9]. We observed healthy follicles (3 to 5 mm and 8 to 10 mm) in ovaries without follicles greater than 25 mm in diameter.…”
Section: Samplesmentioning
confidence: 92%
See 1 more Smart Citation